2013
DOI: 10.1093/jac/dkt426
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of HIV-1 coreceptor tropism by single and triplicate HIV-1 RNA and DNA sequencing in patients undergoing successful first-line antiretroviral therapy

Abstract: ObjectivesMaraviroc has been shown to be effective in patients harbouring CCR5-tropic HIV-1. While this CCR5 antagonist has initially been used in salvage therapy, its excellent safety profile makes it ideal for antiretroviral treatment simplification strategies in patients with suppressed plasma viraemia. The aim of this study was to compare HIV-1 tropism as detected in baseline plasma RNA and peripheral blood mononuclear cell (PBMC) DNA prior to first-line therapy and to analyse tropism evolution while on su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
3
7
0
1
Order By: Relevance
“…A potential explanation for this phenomenon could be low level viral replication that was below the limit of quantitation (80 copies/mL) of the plasma viral load assays used in the WIHS. It is also consistent with some viral replication persisting in cells during viral suppression in plasma [ 21 , 26 ]. Clonal expansion of latently infected cells during suppressive ART has also been described [ 27 ].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…A potential explanation for this phenomenon could be low level viral replication that was below the limit of quantitation (80 copies/mL) of the plasma viral load assays used in the WIHS. It is also consistent with some viral replication persisting in cells during viral suppression in plasma [ 21 , 26 ]. Clonal expansion of latently infected cells during suppressive ART has also been described [ 27 ].…”
Section: Discussionsupporting
confidence: 76%
“…This phenomenon could potentially alter the proportion of non-R5 virus over prolonged periods of virologic suppression. Two other studies that investigated tropism evolution in suppressed patients found lower rates of tropism switching of 7.1% (N = 128, median suppression 4 years) [ 28 ] and 9.5% respectively (N = 42, median suppression 2 years) [ 21 ]. These studies however, were performed on more recently supressed patients, used a viral load cutoff of 50 copies/mL and included both male and female subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as disease progresses, CXCR4 utilizing viruses emerge in about 50% of infected individual [41][42][43]. By Variation at the GPGQ Crown motif (%) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 and large, in Africa Maraviroc is prescribed mostly for patients who have failed first and second line regimens, which are comprised of nucleoside reverse transcriptase inhibitors, non-nucleoside reverse transcriptase inhibitors, and protease inhibitors [44,45]. Since, HIV-1-C drives the epidemic in Southern Africa and accounts for about 46% of infections worldwide [24], the current investigation was aimed at determining the distribution of R5 and X4 viruses in early versus chronic infections in HIV-1-C acquired through MTCT and heterosexual routes in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Vários estudos foram realizados para avaliar o uso de DNA a partir de células monucleares do sangue periférico (PMBCs) para testes de tropismo genotípico. A concordância entre resultados de RNA de HIV-1 plasmático e DNA proviral de PMBCs variou de 85% a 100%, demonstrando a contemporaneidade entre as populações virais nestes espécimes, no contexto de tropismo viral (Meini et al, 2014;Paar et al, 2011;Prosperi et al, 2010;Saracino et al, 2007). Verificouse, ainda, que a produção de vírus R5 e X4 e as subpopulações virais encontradas no sangue periférico são produzidas por células com duração de vida semelhantes e não são geneticamente isoladas de um tipo particular de células (Ince et al, 2009).…”
Section: Bayesian Networkunclassified